Iatrogenic Obturator Hernia with Ureter as Content – a Case Report - Alagappan, Alamelu; Nayak, Manoj Kumar; Tripathy, Sambit; Sahoo, Biswajit; Sahani, Debabrata (Acta medica Lituanica, 2025)
A male in his early 70s presented with complaints of bilateral flank pain for seven months, hematuria for 2 days along with the passage of clots associated with an increased frequency of urination and nocturia. The patient had a history of deep vein thrombosis and was on anticoagulation. On ultrasound, multiple calculi with posterior acoustic shadowing were seen in bilateral kidneys, corroborated by Computed Tomography (CT) urography. Laser lithotripsy with DJ stent placement was conducted. The follow-up CT urography showed an inferiorly displaced DJ stent within the right distal ureter and the DJ stent herniating through the right obturator foramen. The right-sided DJ stent was removed after a month. For obturator hernia, the patient is being kept in the follow-up. This case report reviewed the literature and discussed the diagnosis and complications associated with the obturator hernia with the ureter as the content.